A Study on Job Satisfaction and Burnout Levels of Veterinarians in Türkiye - Seda Çavuş Alan; Rahşan Özen; Abdullah Özen; Abdullah Eryol (Veterinary Medicine and Science)
ABSTRACT Background Burnout is among the most common problems faced in the veterinary profession, which is in constant contact with animals and people. It is already known that job satisfaction is the leading factor that affects professional burnout. Objectives The present study aimed to determine the job satisfaction and burnout levels of veterinarians working in Türkiye, to uncover the factors that might affect job satisfaction and burnout levels and to understand whether there is a relationship between job satisfaction and burnout levels. Methods This cross‐sectional study was conducted with 2276 veterinarians using the Maslach Burnout Inventory and the Minnesota Satisfaction Questionnaire. Results It was found that participants who were older, who had more years of experience in the profession, who were parents and who had higher incomes had lower burnout levels. Job satisfaction was mainly influenced by income level. Working in academia was found to be associated with lower levels of burnout, whereas working in a municipality was associated with higher levels of burnout. It was also found that having chosen the profession willingly and thinking of wanting to be a veterinarian again if given the chance was associated with lower levels of burnout and higher job satisfaction. Conclusion It has been concluded that job satisfaction and burnout levels in veterinarians affect each other.